SPONDILITIS TUBERKULOSIS MULTILEVEL NONKONTINYU PADA SEGMEN SERVIKAL DAN LUMBAL - Arthur Hendrik Philips Mawuntu,* Widi Widowati,** Herlyani Khosama* (NEURONA, 2015)
SPONDYLITIS AFFECTING THE CERVICAL SEGMENT IS REPORTED IN 10 OF ALL TUBERCULOUS SPONDYLITIS CASES AS A RESULT PATIENTS WITH COMPRESSIVE MYELOPATHY IN THE CERVICAL SEGMENT IS OFTEN DIAGNOSED WITH OTHER DISEASES SIMILARLY MULTILEVEL NONCONTIGUOUS TUBERCULOUS SPONDYLITIS IS RARE THIS FORM IS BELIEVED TO BE ASSOCIATED WITH IMMUNODEFICIENCY CONDITIONS DUE TO VARIOUS ETIOLOGIES